Embedding Local Wisdom in Digital Formative Assessment: Students' Experiences with Wayground in Indonesian Elementary Schools - Ni Wayan Bella Berliani; Ida Ayu Made Sri Widiastuti; I Gde Putu Agus Pramerta; Ida Bagus Nyoman Mantra (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
The growing use of digital formative assessment often overlooks cultural contexts, particularly in multicultural nations like Indonesia. Anchored in culturally responsive pedagogy, this study addresses the gap between global digital assessment tools and locally relevant educational practices. This study aims to examine students' experiences of integrating local wisdom into digital formative assessment through Wayground in Indonesian elementary schools. Using a qualitative phenomenological approach, data were gathered via semi-structured interviews and classroom observations with students who consistently used Wayground for formative assessment activities integrating local wisdom. The data were thematically analyzed. Findings indicate that incorporating local wisdom promotes meaningful learning by linking academic content to students' daily experiences. Students reported heightened engagement and motivation, diminished assessment anxiety, and more favorable emotional responses when cultural contexts were recognizable. Culturally contextualized feedback supported reflection and deeper learning. Furthermore, integrating local wisdom strengthened identity affirmation and cultural pride, demonstrating that digital assessment can promote character development alongside cognitive growth. This study concludes that culturally integrated digital formative assessment enhances learning, engagement, and identity development. It is recommended that educators incorporate local wisdom into digital assessment design, that policymakers align digital assessment initiatives with cultural preservation, and that future research employ mixed-methods designs across diverse contexts. Penerapan asesmen formatif digital yang semakin berkembang sering mengabaikan konteks budaya, khususnya di negara multikultural seperti Indonesia. Berlandaskan pedagogi responsif budaya, penelitian ini mengatasi kesenjangan antara alat asesmen digital global dan praktik pendidikan yang relevan secara lokal. Penelitian ini bertujuan mengkaji pengalaman siswa dalam mengintegrasikan kearifan lokal ke dalam asesmen formatif digital melalui Wayground di sekolah dasar Indonesia. Menggunakan pendekatan kualitatif fenomenologis, data dikumpulkan melalui wawancara semi-terstruktur dan observasi kelas terhadap siswa yang rutin menggunakan Wayground dalam asesmen formatif yang memuat kearifan lokal. Data dianalisis secara tematik. Hasil penelitian menunjukkan bahwa integrasi kearifan lokal mendorong pembelajaran bermakna dengan mengaitkan materi akademik dengan pengalaman sehari-hari siswa. Siswa menunjukkan peningkatan keterlibatan dan motivasi, penurunan kecemasan, serta respons emosional positif ketika konteks budaya familiar. Umpan balik yang dikontekstualisasikan secara budaya mendukung refleksi dan pembelajaran mendalam. Selain itu, integrasi kearifan lokal memperkuat identitas dan kebanggaan budaya siswa. Penelitian ini menyimpulkan bahwa asesmen digital terintegrasi budaya meningkatkan pembelajaran, keterlibatan, dan pengembangan identitas. Direkomendasikan agar pendidik mengintegrasikan kearifan lokal dalam desain asesmen digital, pembuat kebijakan menyelaraskan asesmen digital dengan pelestarian budaya, dan penelitian selanjutnya menggunakan metode campuran di berbagai konteks.